Climate-change effects on wind resources in Europe and North America based on the Shared Socioeconomic Pathways - Abel Martinez; Gregorio Iglesias (Journal of Sustainable Development of Energy, Water and Environment Systems)

(untitled)
The long-term evolution of wind resources under climate change is investigated and discussed in the two largest markets of the Western world: Europe and North America. Wind speed projections from the Coupled Model Intercomparison Project 6 are employed considering the Shared Socioeconomic Pathways, the most up-to-date and elaborate climate scenarios proposed by the Intergovernmental Panel on Climate Change – specifically, a middle-of-the-road scenario and an augmented emissions scenario. In Europe, projections indicate a widespread, substantial decline in wind resources (~15% in wind power density). Whereas an overall decrease in wind energy is also anticipated in North America, this appears to be highly concentrated in different foci. Additionally, the evolution of wind resources in this continent is projected to be notably season-dependent, with strong increases of over 60% and decreases of up to 50%. Conversely, the evolution in Europe shows changes of lesser magnitude but more constant throughout the year.